Preface - Stupkiewicz, S. (Archives of Mechanics, 2023)
This issue of Archives of Mechanics contains a selection of papers presented at the CMM-SolMech 2022 conference held in Swinoujscie, Poland, September 5–8, 2022. The conference was a joint event encompassing the 24th International Conference on Computer Methods in Mechanics (CMM) and the 42nd Solid Mechanics Conference (SolMech).